Ethnobiology of plant and animal-based foods among the Bajo People in Gorontalo, Indonesia - MARGARETHA SOLANG; MUHAMMAD ISRA; JUSNA AHMAD; SYAM S. KUMAJI; MUHAMMAD NUR AKBAR; MARGARETA RAHAYUNINGSIH; ENNI SUWARSI RAHAYU; ADITYA MARIANTI; SUJATHA RAMASAMY (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Solang M, Isra M, Ahmad J, Kumaji SS, Akbar MN, Rahayuningsih M, Rahayu ES, Marianti A, Ramasamy S. 2026. Ethnobiology of plant and animal-based foods among the Bajo People in Gorontalo, Indonesia. Biodiversitas 27 (2): d270226. https://doi.org/10.13057/biodiv/d270226. Indigenous communities maintain complex food systems that are closely linked to local biodiversity and traditional ecological knowledge (TEK). This study documents the ethnobiological knowledge of the Bajo people in Gorontalo, Indonesia, focusing on the diversity and culturally perceived functions of plant and animal-based foods. Fieldwork was conducted from April to June 2025 using semi-structured interviews, direct observation, and participatory approaches in three coastal villages. A total of 54 informants (37 men and 17 women, aged 35-76 years) reported the use of 25 species, comprising 11 plant species and 14 animal species, utilized for food, medicinal, and ritual purposes. Frequently cited species included Tacca leontopetaloides (ubi teo), Tridacna sp. (kima), Sesuvium portulacastrum (gaganga), Holothuria scabra (tripang putih), and Caulerpa lentillifera (lato). Quantitative ethnobiological indices indicated high cultural salience of T. leontopetaloides, which recorded the highest Relative Frequency of Citation (RFC = 0.78) and Use Value (UV = 0.82), followed by Tridacna sp. (RFC = 0.62; UV = 0.70). Traditional preparation techniques, including fermentation, boiling, and raw consumption, reflect adaptive strategies developed to optimize food use and culturally perceived health-related benefits. Although only a limited number of informants explicitly used the term “functional food,” local practices demonstrate an implicit understanding of the relationship between food and health. This study highlights how biodiversity, traditional ecological knowledge, and subsistence practices intersect within the Bajo food system, underscoring the relevance of ethnobiological knowledge for sustaining community-based food systems and supporting biodiversity conservation.